Roadmap for the treatment of heart failure patients after hospital discharge: an interdisciplinary consensus paper (Swiss Medical Weekly, 2020)
The transition period from the hospital to the outpatient setting is a critical phase when managing heart failure. A well-structured transition is paramount and helps to ensure a tight follow-up schedule for the heart failure patient, thereby improving treatment outcomes. This article aims to provide guidance for the first three follow-up visits after hospital discharge, with a focus on monitoring heart failure patients and up-titrating their medication in primary care.